ANALISIS ETIKA BISNIS ISLAM DAN KUALITAS PELAYANAN DALAM KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA BANK TABUNGAN NEGARA (BTN) SYARIAH CABANG BOGOR (IAIN Tulungagung, 2018)
Abstract: The development of sharia banking is still not satisfactory when compared with the development of conventional banking. The relatively lowgrowth of sharia banking market share is due to the low level of customersatisfaction and loyalty for sharia banking. This study aims to determinethe influence of Islamic business ethics and service quality to customersatisfaction and loyalty Bank BTN Syariah Branch Bogor. In this study,the data obtained from the dissemination of questionnaires to 100customers of Bank BTN Syariah Branch Bogor, obtained by using simplerandom sampling, then analyzed by using quantitative data analysis.Quantitative analysis includes validity test, reliability test, classicalassumption test, path analysis, hypothesis testing through t test andcoefficient of determination (R2) while data processing using SPSS 23.0 forwindows. From result of research of research data got 2 result of value of Rsquare, first obtained equal to 0,245 indicate level of customer satisfactionor customer BTN Syariah Branch 24,5% influenced by implication ofIslamic business ethics and service quality executed by institution, while the rest equal to 75,5 % influenced by other variables not included in thisresearch. The second R square value obtained by 0.438 shows the level ofcustomer loyalty or customer BTN Sharia Branch of Bogor 43.8%influenced by the implication of Islamic business ethics and service qualityimplemented by the institution, while the remaining 56.2% is influenced byother variables that are not included in this research. The results showedthat partially Islamic business ethics variables have a positive effect is notsignificant to customer loyalty with t arithmetic 0.469 with a significancelevel of 0.64 above 0.05. Variable of service quality have positive andsignificant influence to customer loyalty with t arithmetic 4,512 with significance level 0,00 below 0,05. While Islamic business ethics variableshave a positive and significant influence on customer loyalty with tarithmetic 4.104 with a significance level of 0.00 below 0.05. Servicequality variable has positive and significant influence to customer loyaltywith t arithmetic 5,218 with significance level 0,00 below 0,05. Customersatisfaction variable has a positive and significant influence on customerloyalty with t arithmetic 3,542 with a significance level of 0.01 below 0.05.